Selective deactivation of serum IgG: a general strategy for the enhancement of monoclonal antibody receptor interactions. - Baruah, K; Bowden, T; Krishna, B; Dwek, R; Crispin, M; Scanlan, C (2012)
Serum IgG is a potent inhibitor of monoclonal antibody (mAb) binding to the cell-surface Fcγ receptors (FcγRs), which mediate cytotoxic and phagocytic effector functions. Here, we show that this competition can be eliminated, selectively, by the introduction to serum of (i) an enzyme that displaces Fc from FcγRs and (ii) a modification present in the therapeutic mAb that renders it resistant to that enzyme. Specifically, we show that (i) EndoS (endoglycosidase S) cleaves only complex-type glycans of the type found on IgG but (ii) is inactive against an engineered IgG Fc with oligomannose-type glycans. EndoS thus reduces FcγR binding of serum IgG, but not that of engineered mAb. Introduction of both the engineered mAb and endoglycosidase in serum leads to a dramatic increase in FcγR binding compared to the introduction of mAb in serum alone. Antibody receptor refocusing is a general technique for boosting the effector signal of therapeutic antibodies.